Implementasi Keteladanan Guru PAI dalam Pembinaan Akhlak Siswa di SMAN 5 Bukittinggi - Agus Salim; Imamuddin Imamuddin (YASIN, 2026)
The exemplary conduct of Islamic Religious Education (PAI) teachers in fostering students’ moral character has received attention in various previous studies, but studies that specifically discuss its implementation in the context of public schools and the dynamics of supporting and inhibiting factors remain limited. This study aimed to explore in depth the implementation of PAI teachers’ exemplary conduct in fostering students’ moral character at SMAN 5 Bukittinggi. This study used a qualitative approach with a case study design. The research participants consisted of PAI teachers, students, and school personnel selected using purposive sampling. Data were collected through observation, interviews, and documentation, and were then analyzed using thematic analysis techniques through the stages of data reduction, data display, and conclusion drawing. The results showed that PAI teachers’ exemplary conduct was implemented in various dimensions, including worship, personal morality, communication, discipline, social interaction, and behavioral consistency, which had a positive impact on students’ moral development. However, several student moral problems were still found to be influenced by external factors, such as social media, as well as teachers’ limited time to provide intensive guidance. This finding contributes to the development of Islamic education theory and social learning by expanding understanding of exemplary conduct-based moral character development in the context of modern education. Thus, teachers’ exemplary conduct is a key factor in fostering students’ moral character, so schools need to strengthen religious culture and improve supervision of external influences that may affect students’ behavior.